Brain gene expression changes elicited by peripheral vitellogenin knockdown in the honey bee. Issue 5 (24th July 2013) - Wheeler, M. M.; Ament, S. A.; Rodriguez‐Zas, S. L.; Robinson, G. E.
Abstract: Vitellogenin (Vg) is best known as a yolk protein precursor. Vg also functions to regulate behavioural maturation in adult honey bee workers, but the underlying molecular mechanisms by which it exerts this novel effect are largely unknown. We used abdominal vitellogenin ( vg ) knockdown with RNA interference (RNAi) and brain transcriptomic profiling to gain insights into how Vg influences honey bee behavioural maturation. We found that vg knockdown caused extensive gene expression changes in the bee brain, with much of this transcriptional response involving changes in central biological functions such as energy metabolism. vg knockdown targeted many of the same genes that show natural, maturation‐related differences, but the direction of change for the genes in these two contrasts was not correlated. By contrast, vg knockdown targeted many of the same genes that are regulated by juvenile hormone (JH) and there was a significant correlation for the direction of change for the genes in these two contrasts. These results indicate that the tight coregulatory relationship that exists between JH and Vg in the regulation of honey bee behavioural maturation is manifest at the genomic level and suggest that these two physiological factors act through common pathways to regulate brain gene expression and behaviour.